1976
DOI: 10.1177/24.1.815428
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyribonucleic acid replication in single cells and chromosomes by immunologic techniques.

Abstract: Antibodies to 5-bromodeoxyuridine (BrdU) or iododeoxyuridine may be used to identify cells or regions of chromosomes in which de novo deoxyribonucleic acid synthesis has occurred. The antibodies to BrdU were produced in rabbits by injection of the antigen, a conjugate between bovine serum albumin and bromouridine (BrU), or iodouridine. Specific antibodies were produced by affinity chromatography on AH-Sepharose 4B to which had been coupled BrU. Anti-BrU cross-reacts with iodeodeoxyuridine. Indirect antibody te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

1978
1978
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 13 publications
0
14
0
3
Order By: Relevance
“…However, few studies have been performed under physiological conditions [5]. In order to establish the time of initiation of proliferation (S phase entry) in uterine epithelia during the estrus-metestrus transition, we performed time course experiments using BrdU incorporation [43]. We observed that 30% of the glandular epithelial cells are in S phase at 00:00 h of metestrus day, while in the luminal epithelium 10% of the cells are in S phase at 03:00 h of metestrus ( Figs.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have been performed under physiological conditions [5]. In order to establish the time of initiation of proliferation (S phase entry) in uterine epithelia during the estrus-metestrus transition, we performed time course experiments using BrdU incorporation [43]. We observed that 30% of the glandular epithelial cells are in S phase at 00:00 h of metestrus day, while in the luminal epithelium 10% of the cells are in S phase at 03:00 h of metestrus ( Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The following markers were used to identify proliferating cells: 1) Ki67, which is expressed by all actively cycling cells (Gerdes et al, 1983); 2) the thymidine analogue bromodeoxyuridine (BrdU), which is incorporated into proliferating cells in the S-phase of the cell cycle (Gratzner et al, 1976; Miller and Nowakowski, 1988; del Rio and Soriano, 1989); and 3) phosphorylated histone H3, which is expressed by cells in the M-phase of the cell cycle (Hendzel et al, 1997). In sections doubly labeled for Ki67, BrdU, or phosphorylated histone H3 and NG2 from five, five, and one mouse, respectively, the total number of cells positive for Ki67, BrdU, or phosphorylated histone H3 and the number of cells doubly labeled for Ki67, BrdU, or phosphorylated histone H3 and NG2 was counted.…”
Section: Methodsmentioning
confidence: 99%
“…Cell labelling with BUDR can be accomplished not only in vitro but also in vivo, since BUDR is neither radioactive nor myelotoxic at the doses needed for this type of study, and it is also employed as an anticancer drug (Bagshaw et al, 1967;Hoshino & Sano, 1969;Russo et al, 1984). Furthermore, the immunoreaction products have a high resolution without the background noise that is (Gratzner et al, 1976), acetone (Morstyn et al, 1983) or 70% ethanol (Hamada, 1985. One limitation of this technique is that it cannot be applied when tissues needed to be fixed with aldehydes (for electron microscopy or for the immunohistochemical detection of certain kinds of antigens) (Kirkpatrick & D'Ardenne, 1984), or simply when tissues are fixed routinely for conventional histology.…”
Section: Introductionmentioning
confidence: 99%